Cranial nerves bridging the middle ear and cerebellum causing cerebellar peduncle abscess: A case report - Shrestha, Prabin; Sandhu, Mani Ratnesh S; Jensen, Katherine J; Shidoh, Satoka; Yamaguchi, Satoshi (Acta radiologica open, 2024)
Cerebellar abscess is a reported complication of chronic suppurative otitis media (CSOM) and is life threatening at times. It usually develops by direct spread of CSOM through the bony erosion in the petrous bone or by thrombophlebitis of the sigmoid sinus. However, an alternative pathway of infection transmission from the petrous bone to the cerebellum through the anatomical bridge of the cranial nerves has possibly not been described before. A 63-year-old female patient with CSOM and cholesteatoma developed ataxia and right facial palsy. Computed tomography (CT) showed bone erosion of the right petrous bone suggesting middle ear infection. Post-contrast MRI revealed an enhancement of swollen 7th/8th nerve complex, suggesting neuritis, and cholesteatoma in the right petrous bone. It also showed ring enhancing lesion in the cerebellar peduncle of the same side suggesting brain abscess. Surgical intervention was performed emergently and pus aspirated. She also underwent mastoidectomy and removal of cholesteatoma later by the otolaryngology team and finally got better. This case illustrates that CSOM can cause cerebellar abscess by spreading infection via anatomical bridge of the cranial nerves without direct invasion from the temporal bone or thrombophlebitis of sinus.